Towards a Circular Spare Parts Management for Commercial Vehicles: A Framework Proposal for the Case of Batteries - Hermsen, Marius; Niemeyer, Jan Felix; Uhlig, Edith; Mennenga, Mark; Herrmann, Christoph (Procedia CIRP, 2025)
The importance of electric vehicles is steadily increasing in times of climate change. While the focus was initially on private cars, the area of commercial vehicles, especially trucks, becomes increasingly important. Electrically powered trucks offer great potential for reducing greenhouse gas emissions in goods transport. However, the environmental impact of electric vehicle batteries poses a critical challenge, necessitating effective strategies for managing their circular economy. Due to their significant weight and complex storage, supply, and retrieval processes, unique logistical and operational issues arise. Efficient spare parts management is crucial, especially since specialized battery storage facilities are often distant from the points of use. This paper proposes a comprehensive framework to enhance circular supply in spare parts management, with a focus on heavy-duty electric trucks. Given the scarcity of research on circular spare parts management in the existing literature, a comprehensive structured literature review was undertaken. Insights from this review guided the creation of the proposed framework, using battery lifecycle management in the trucking sector as a representative example. Furthermore, expert interviews were conducted to validate its practicality. The paper concludes with suggestions for advancing sustainable electric vehicle battery management practices.